Customer satisfaction and loyalty towards grocery stores in Palestine - Abusharar, Majed M. M.; Haque, Ahasanul; Jan, Tahir (IIUM Press, International Islamic University Malaysia, 2017)
Notably, grocery stores are crucial to the retail industry sphere. They are known as important links in the food distribution system. Some grocery stores have made great strides to work with local producers to benefit consumers and communities as a whole. Palestine, seemingly, has been seen as an exceptional marketplace as the Palestinians have found as time went by, how to bridge between local produce locally and the local market, under certain circumstances. Local producers can market their products via grocery stores and consider establishing a trustworthy relationship with their customers. Although customer loyalty to grocery stores has been extensively studied across the world, Palestine’ grocery market sphere has remained untouched. This case study uncovers the underlying critical influencing factors on consumer loyalty towards grocery products marketing in Palestine. This research used a field survey questionnaire. A structured self-administered questionnaire was deployed and data was collected at the end of 2014. To that end, data collection and data analysis procedures are then articulated and the choice of Structural Equation Modeling (SEM) is explained. The findings reveal key parameters of brand strategies along with the relationship and the impact of these strategies as well as other research factors. Concurrently, this study contributes to both grocery store managers and the Palestinian government’s aim to realise the perception of the Palestinians about the influential factors that might help them make decisions for future policies on food and other grocery products.